Cumulative experience and long term follow-up of pentostatin-based chemoimmunotherapy trials for patients with chronic lymphocytic leukemia. Issue 4 (3rd April 2018) - Kay, Neil E.; LaPlant, Betsy R.; Pettinger, Adam M.; Call, Timothy G.; Leis, Jose F.; Ding, Wei; Parikh, Sameer A.; Conte, Michael J.; Bowen, Deborah A.; Shanafelt, Tait D.
ABSTRACT: Background : 7 regimens of pentostatin based chemoimmunotherapy (CIT) for progressive previously untreated CLL primarily with long term follow-up to update both efficacy and toxicity. Research design and methods : Prognostic markers including assessment of IGVH and FISH status were done on all. Response rates and 95% binomial confidence intervals were calculated for each regimen and in the combined cohort. Overall survival and treatment-free survival were evaluated using Kaplan-Meier methods. Results : The initial CIT trial was pentostatin (2 mgs/m2), cyclophosphamide (600 mg/m2) and rituximab (PCR) but subsequent P based CIT trials with modifications in subsequent trials. The cohort (n = 288) included 52% with unmutated IGVH status and del17p (4.5%) and del11q (14.9%). Toxicity profiles were primarily hematologic and no patient has developed MDS or AML after a median follow-up of 6.4 years. The overall response rate across all trials was found to be over 90% with a 41% complete response rate. We validated that the CLL IPI model segregates progressive CLL patients into 4 risk groups associated with OS and TFS. Conclusions : The high overall and complete response levels in favorable genetic risk CLL along with favorable toxicity profiles provide rationale for consideration of a PC based strategy for previously untreated progressive CLL.